Asymmetrical tidal tails of open star clusters: stars crossing their cluster's práh† challenge Newtonian gravitation. Issue 3 (26th October 2022) - Kroupa, Pavel; Jerabkova, Tereza; Thies, Ingo; Pflamm-Altenburg, Jan; Famaey, Benoit; Boffin, Henri M J; Dabringhausen, Jörg; Beccari, Giacomo; Prusti, Timo; Boily, Christian; Haghi, Hosein; Wu, Xufen; et al.
ABSTRACT: After their birth a significant fraction of all stars pass through the tidal threshold (práh) of their cluster of origin into the classical tidal tails. The asymmetry between the number of stars in the leading and trailing tails tests gravitational theory. All five open clusters with tail data (Hyades, Praesepe, Coma Berenices, COIN- Gaia 13, NGC 752) have visibly more stars within $d_{\rm cl}≈ 50\, {\rm pc}$ of their centre in their leading than their trailing tail. Using the Jerabkova-compact-convergent-point (CCP) method, the extended tails have been mapped out for four nearby 600–2000 Myr old open clusters to $d_{\rm cl} > 50\, {\rm pc}$ . These are on near-circular Galactocentric orbits, a formula for estimating the orbital eccentricity of an open cluster being derived. Applying the Phantom of Ramses code to this problem in Newtonian gravitation the tails are near-symmetrical. In Milgromian dynamics (MOND), the asymmetry reaches the observed values for 50 < d cl /pc < 200 being maximal near peri-galacticon, and can slightly invert near apo-galacticon, and the Küpper epicyclic overdensities are asymmetrically spaced. Clusters on circular orbits develop orbital eccentricity due to the asymmetrical spill-out, therewith spinning up opposite to their orbital angular momentum. This positive dynamical feedback suggests Milgromian open clusters to demise rapidly as their orbital eccentricity keeps increasing. Future work is necessary to better delineate the tidal tails around open clusters of different ages and to develop a Milgromian direct n -body code.